2015
DOI: 10.5901/mjss.2015.v6n5s4p503
|View full text |Cite
|
Sign up to set email alerts
|

The Lifestyle in the Development of Ideological Policy

Abstract: The goal of the article consists in understanding Islam as a lifestyle in Europe. The lifestyle is understood through creation and introduction of religious differences and determines the perception of Islam as different from the European values. This fact affects acceptance of the lifestyle as a legitimization of religious subjectness. The conclusion is made that the difficulty of integrating the Muslims into the European community consists in substitution of social issues for ethnocultural and ethnoreligious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…As early as in the 1990s, opinion polls showed that the vacuum that had formed in mass consciousness began to fill with traditionalist ideas as a consequence of a radical change in the established system of social relations and value system. Thus, the visions of freedom as "the possibility of being the architect of one's own fortunes", of democracy as the right to elect a leader for oneself, who receives the full authority to autocratic rule upon his election, which gained fairly widespread currency in the public consciousness at that time, basically ascended to the medieval peasant political culture (Chernous et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As early as in the 1990s, opinion polls showed that the vacuum that had formed in mass consciousness began to fill with traditionalist ideas as a consequence of a radical change in the established system of social relations and value system. Thus, the visions of freedom as "the possibility of being the architect of one's own fortunes", of democracy as the right to elect a leader for oneself, who receives the full authority to autocratic rule upon his election, which gained fairly widespread currency in the public consciousness at that time, basically ascended to the medieval peasant political culture (Chernous et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Проявление архаики можно рассматривать как отражение слабой готовности российского общества к инновациям, возможным рискам, связанным с изменениями, что и способствует стремлению найти опору не только в привычных формах общественного бытия, но и в глубинных архетипах массового сознания [10], и тогда рутинизация принимает характер социальной рестав-рации. Если мы обратимся к коллективной монографии «"Советское наследство".…”
unclassified